Herding Behavior, Loss Aversion Bias, Financial Literacy, and Investment Decisions (a Study on Millennial Generation in Indonesia in the Digital Era) - Aprilianti, Anti Azizah; Tanzil, Nanny Dewi; Pratama, Arie (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
In the last few years in Indonesia, many investment applications have emerged where these applications make it easy for investors to be able to invest. The emergence of investment applications also raises many problems such as fraud under the guise of investment and people in Indonesia, especially young people who are easily tempted by investment offers that provide high returns so that they often carry out investment activities but are irrational and tend not to look at financial conditions in making investments. The purpose of this study is to see how the internal and external factors of an investor, especially the millennial generation, in making investment decisions, namely the factors of Herding Behavior, Loss Aversion Bias and Financial Literacy. This research method uses descriptive and verification methods with a sample size of 400 respondents and data analysis techniques using Multiple Logistic Regression Analysis. The results showed that the the Herding Behaviour variable has a positive effect on Investment Decisions of the Millennial Generation in Indonesia in the Digital Age, Loss Aversion Bias has a negative effect on Investment Decisions of the Millennial Generation in Indonesia in the Digital Age, while the Financial Literacy variable has no effect on Investment Decisions of the Millennial Generation in Indonesia in the Digital Age.